Metamorfoses da estética da mercadoria: implicações do fetichismo da mercadoria para as negociações identitárias de modelos comerciais - Lisbão, Yuri Marcondes (2017)
This work aims to understand, from the perspective of critical social psychology, the metamorphoses of the commodity aesthetics and the implications of fetishism in the development and the identity negotiations of Brazilian women's commercial models. The research revolves around the following problematization: the model work – which summons the construction of a specific character among so many others who composes the identity – often ends up being experienced (and recognized) as the totality of the identity. So, since the model is worth its appearance and its body as merchandise, how do these women negotiate, everyday, the representation of this character? To take account of this issue, through the usef life-story narratives, this research, on a qualitative character, is circumscribed between the empirical and theoretical fields, weaves some articulations on the dynamics of relationships, interactions and negotiations identity of these models. It is believed that in the capitalist society of consumption, as it is contemporary, this theme is relevant and current, since it deals with discussing how the effects of the market have interfered in the way the identity process has occurred. And although the model profession explains the transformation of people into commodities, the processes of fetishism, reification and the (im)possible forms of recognition contained therein can be identified in large part of the professions that serve the mode of capitalist production